Maternity leave and paternity leave - Abdul Kadir, Adibah; Maulad Bahrol, Khadijah; Humaid Alhosani, Adnan Ali Hassan; Ismail, Fadillah (Penerbit Uthm, 2019)
Generally, maternity leave is a time of holiday given to women before and after childbirth. The leave is being given to the women to care for new-born child. This leave also for the mother to recover themselves after having an operation to having their child. Maternity leave also includes a leave before the expected birth. This is because to give a chance for the mother to have last preparation and wait until the last moment, so they can maximize their time with the baby once it arrives.